Bahasa Inggris - Chesa Defista; Nurfina Aznam (Jurnal Penelitian Pendidikan IPA, 2024)
Research related to conceptual understanding is often carried out, such as the influence of a model on conceptual understanding, or knowing students' level of understanding of chemistry concepts. However, there has been no systematic reflection on chemistry research focused on conceptual understanding. Based on this, this research aims to systematically synthesize articles related to chemistry focused on research trends in conceptual understanding with the year range of articles used 2014-2023. After conducting a national and international data search using keyword patterns (e.g., Pattern 1: conceptual and chemical understanding), 48 research papers emerged for systematic review. Then, primary and secondary codes were created by the authors for the research paper. The systematic review showed a variety of research scopes (e.g., relevance of chemistry education models) and dominant research focus for different themes (e.g., competencies and variables related to objectives, variables, samples, chemistry concepts, and conclusions). Furthermore, it was revealed that research on understanding chemical concepts includes various research fields.